2008
DOI: 10.1143/jjap.47.6566
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Estimating Impact Strength of Solder-Ball-Bonded Interfaces in Semiconductor Packages

Abstract: A method for estimating the impact strength of a solder ball junction in encapsulated semiconductor packages was developed. This method reveals the impact force in a solder ball unit and the time required for a solder ball to break. The bombardment absorbed energy required for the ball to break is evaluated as impact strength. This method can be used to quantitatively evaluate the impact strength of solder ball junctions, which is difficult to do using conventional shear and tensile strength estimation methods. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is forecast that SiC devices-which are expected to be used in environments at 250 C and over-will be able to solve this problem of reduced reliability due to the remelting and intermetallic-compound growth that plagues bonding with conventional tin-based solders. 2) It is also known that when the size of fine metallic particles reaches several nanometers, their apparent melting point becomes lower than that of their bulk material. 3,4) This is assumed to be caused by a phenomenon whereby, when particle size decreases, the surface energy corresponding to the particle size (i.e., surface tension) becomes enormous and, as a result, particles that contact one another quickly fuse together (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is forecast that SiC devices-which are expected to be used in environments at 250 C and over-will be able to solve this problem of reduced reliability due to the remelting and intermetallic-compound growth that plagues bonding with conventional tin-based solders. 2) It is also known that when the size of fine metallic particles reaches several nanometers, their apparent melting point becomes lower than that of their bulk material. 3,4) This is assumed to be caused by a phenomenon whereby, when particle size decreases, the surface energy corresponding to the particle size (i.e., surface tension) becomes enormous and, as a result, particles that contact one another quickly fuse together (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, 14,15 high-speed testing (i.e., at more than 10 mm/s) is a more effective method for the measurement of impact fracture strength in solder joints. Morita et al 16 reported that the effect of Kirkendall voids on Sn-Ag-Cu/Cu solder joints was more evident with high-speed than low-speed testing. Therefore, in this study, the high-speed impact test was employed to evaluate the reliability of Sn-3.0Ag-0.5Cu solder joints with Ti/Ni(V)/Cu UBM, and the effect of Sn-patch on reliability is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[5][6][7][8] Morita et al proposed a miniature impact test to evaluate impact reliability by adopting the principle of the classic Charpy impact test. [9] This test has been used by various researchers to evaluate impact reliability. [2,[10][11][12] It is reported that both the solder hardness and the intermetallic compound (IMC) layer at the interface affect the impact reliability of the solder joint.…”
Section: Introductionmentioning
confidence: 99%
“…[2,[10][11][12] It is reported that both the solder hardness and the intermetallic compound (IMC) layer at the interface affect the impact reliability of the solder joint. [1,3,9,[13][14][15] The formation of the interfacial IMC layer between the solder and the under-bump metallurgy (UBM) is essential in the manufacturing of reliable solder joints. However, the impact reliability of the solder joint decreases with increasing thickness of the interfacial IMC layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation